Implementasi Strategi Bimbingan Manasik Haji Di Masa Pandemi Covid-19 - Fitriani, Putri Diesy; Awalludin, Fakhri; Azzaahra, Raisa Agnia (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2022)
The purpose of this study was to determine the implementation of the Hajj ritual strategy during the COVID-19 pandemic. The method used in this research is a descriptive research method using a qualitative approach in which data is collected in various ways, such as interviews with the KBIH as well as field observations and analyzing data from various data sources that have been obtained. The results of this study are related to the implementation of the Hajj ritual strategy during the COVID-19 pandemic, carried out in 3 ways, namely online, offline and also hybrid. In addition, in implementing the strategy for implementing Hajj rituals, the Ministry of Religion, in this case the Director General of Hajj and Umrah Organizers, publishes a Guidebook for Hajj and Umrah Manasik During a Pandemic Period. Moreover, related to the implementation at the KBIH Qiblat Tour, the implementation of Hajj services is carried out online with various strategies such as delivering material that is carried out clearly, interesting manner and understand the conditions of the congregation from various circles.